Comprehensive Comparison of Two Fault Tolerant Axial Field Modular Flux-Switching Permanent Magnet Machines with Different Stator and Rotor Pole-Pairs Combinations - Yixiang Tu; Mingyao Lin; Keman Lin; Yong Kong; Da Xu (Machines, 2022)
This paper gives a comprehensive comparison among two fault-tolerant axial field modular flux-switching (AFFSPM) machines with different stator modular segments (U- and E-core) and stator-slots/pole-pairs combinations. The topologies of two AFFSPM machines are introduced, each with two feasible stator slots and rotor pole-pairs combinations with high winding factors based on the slot-conductor back-EMF star vectors theory. Then, the static performance including the air-gap flux density, flux linkage, back-electromagnetic force (back-EMF), and electromagnetic torque are analyzed and compared. Moreover, the fault-tolerant capability is then investigated by the torque performance under one- and two-phase open-circuit conditions in which the corresponding fault-tolerant control strategies are applied. The predicted results confirm that the 6-stator slot/11-rotor-pole-pair E-core AFFSPM machine exhibits the best performance of the four candidates.